Assessment of Radish (Raphanus sativus L.) Cultivars for its Yield and Yield Attributing Characters at Central Mid-Hill (Kathmandu Valley) Conditions of Nepal - Shrestha, Surendra Lal; Ghimire, Dipendra; Shrestha, Yadav Kumar; Gautam, Ishwori Prasad (Nepalese Horticulture, 2021)
A varietal study on five open pollinated cultivars of Radish viz Mino Early, Okura, Pusa Chetki, Forty Days and Miyasige with an objective to find the most superior variety was conducted at Horticultural Research Division, Khumaltar, Lalitpur in winter season for 3 years from 2016 in consecutive years. Mino Early and Forty Days are widely adopted varieties and kept as local check varieties. The trial was conducted under Randomized Complete Block Design (RCBD) with four replications. Out of the five cultivars, Okura gave significantly the highest of Root wt. (326 g), Root yield (53.85 t/ha), Root length (25.5 cm), Root diameter (53.9 mm), and Leaf wt per plant. (268 g), Days to harvest (63 days) followed by Miyasige which had Root wt (259 g), Root length (23.4 cm) Root diameter (51.9 mm), Days to harvest (66 days). Okura had 49 percent yield increment followed by Miyasige with 21.9 percent as compared to Mino Early. Hence, these two cultivars are found superior and recommended for cultivation in central mid-hills like Kathmandu valley conditions in Nepal.